THE ROLE OF ISLAMIC FINANCIAL INSTITUTIONS IN PREVENTING ONLINE GAMBLING PRACTICES - Hilman Dermawan; Bukhari Ali; sholihin, Riadhus (Prodi Hukum Ekonomi Syariah, Fakultas Syariah dan Hukum, UIN Ar-Raniry, 2024)
Islamic Financial Institutions, especially Islamic banks, are a form of business in the financial sector based on sharia principles, and are currently showing a positive growth trend in Indonesia. However, this poses a challenge for the Islamic banking industry to ensure compliance with applicable sharia provisions. Based on current facts, there are several online gambling sites that provide payment and withdrawal options through Islamic bank accounts. This is the problem and purpose of the research, namely how efforts to prevent online gambling practices through Islamic banks, the mechanism of the online gambling system and the elements contained in it, as well as the steps that can be used by Islamic banks to reduce the number of online gambling. The research method used is library research which collects various references from journal articles as reference material, library research relies on literature such as books, notes, or research reports from studies. Based on the results of the research, that in this problem there are two ways that can be used by Islamic banks to prevent online gambling practices, namely by using modern technology owned by the Islamic bank (internal) and cooperating with other authorities (external).